Islamic Worldviews On Corporate Social Responsibility A New Paradigm of Ethical Economics and Prosperity - Taufan Maulamin (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Challenges and role of accountings in the development of human civilization from now on and henceforth is by encouraging human awareness of social responsibility in economic activities, information disclosure, and managing resources productively, efficiently and sustainably, formulating the principles of economic justice, balance of spending and exploitation of resources to achieve mutual prosperity. In the next picture it is hoped that there will be a new balance between the role of the State in the economic field, the role of the corporation, the role of individuals and the role of the public in various social activities. To realize this new balance, challenges must start from corporations to implement sustainable economic activities. This is what is meant by the Islamic worldviews on corporate social responsibility as a new paradigm, namely the practise of ethical economics to achieve mutual prosperity.